Manejo da agrobiodiversidade por pequenos agricultores do agreste da Paraíba: o caso da mandioca (Manihot esculenta Crantz EUPHORBIACEAE). - Mantovani, Ana Laura Bezerra (2009)
Cassava or manioc (Manihot esculentab Crantz) crop is extensively cultivated in most ecological conditions of the Brazilian territory, supported by its great interspecific diversity. Accomplishes an important social role in dry lands of tropical and subtropical regions and represents a weighty energy source for feed security in drought period. The goal of this research is to systemize small farmer s knowledge about Manihot esculenta varieties of the Agreste region in the Brazilian state of Paraíba. Semi-structured interviews and guided visits to three farmers were performed. The interviews enabled the identification of management methods used in cassava crops and sketch the varieties flux between the crops. Each identified variety was characterized by the same parameters used by the farmers to differ each other. The principal indentified parameters were: leafs colors and shapes; young shoot colors; the color of petioles; the color of mature stem; roots skins and barks colors; poise of adult plants. Samples of each variety were collected and photographed to base the comparison between different varieties founded in different properties. Crops showed to be policultures or polivarietal monocultures. Fifty-nine variety names were appointed by farmers, which in 21 are sweet manioc and 38 bitter cassavas. Thirty one still available in the studied crops, 23 are considered lost varieties and 5 able to be found in other properties. Only 3 varieties are common to all informants. On the other hand, 20 types were cultivated by only one farmer. Eighteen are known by all farmers, witch in 2 are considered lost. The results show considerable intra-specific diversity, highlighting the individual dimension of agrobiodiversity management.